2004
DOI: 10.1523/jneurosci.0188-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Odors Detected by Mice Deficient in Cyclic Nucleotide-Gated Channel Subunit A2 Stimulate the Main Olfactory System

Abstract: It is believed that odor transduction in the mammalian main olfactory system only involves the cAMP-signaling pathway. Here, we report on odor responsiveness in mice with a disrupted cyclic nucleotide-gated (CNG) channel subunit A2. Several odorants, including putative pheromones, can be detected and discriminated by these mice behaviorally. These odors elicit responses in the olfactory epithelium, main olfactory bulb, and olfactory (piriform) cortex of CNGA2 knock-out mice. In addition, responses to odors det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
113
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 37 publications
(62 reference statements)
10
113
0
1
Order By: Relevance
“…In addition, MOE responses to MHC peptides are inhibited by adenylcyclase antagonists and critically depend on a functional CNGA4 gene, which encodes a principal subunit of a cyclic AMP-sensitive CNG channel expressed in MOE but not in the VNO, thus showing that MHC peptides ligands are transduced in the MOE by cells employing a cAMP-signaling pathway and the olfactory CNG channel. Similar results have been obtained with the odorant 2-heptanone: its detection appears to be dependent on the Trp2 gene in the VNO, while in the MOE, detection of 2-heptanone depends on the CNGA2 [60,63]. At the behavioral level, this processing of the same olfactory signals is not just a redundancy.…”
Section: Functional Roles Of Both the Main And The Accessory Olfactorsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, MOE responses to MHC peptides are inhibited by adenylcyclase antagonists and critically depend on a functional CNGA4 gene, which encodes a principal subunit of a cyclic AMP-sensitive CNG channel expressed in MOE but not in the VNO, thus showing that MHC peptides ligands are transduced in the MOE by cells employing a cAMP-signaling pathway and the olfactory CNG channel. Similar results have been obtained with the odorant 2-heptanone: its detection appears to be dependent on the Trp2 gene in the VNO, while in the MOE, detection of 2-heptanone depends on the CNGA2 [60,63]. At the behavioral level, this processing of the same olfactory signals is not just a redundancy.…”
Section: Functional Roles Of Both the Main And The Accessory Olfactorsupporting
confidence: 79%
“…Such AC3 KO mice were able to detect several volatile odorants, including putative pheromones, presumably via the VNO. However, more recently it was shown that mice defective in the olfactory cAMP signaling pathway can detect some volatile odorants through their olfactory epithelium using alternative transduction pathways [63].…”
Section: Functional Roles Of Both the Main And The Accessory Olfactormentioning
confidence: 99%
“…By contrast to Ano2 -/-mice, Cnga2 -/y mice 31 showed a clear-cut impairment in the same test (Fig. 8a), as reported 25,30 . Discrimination ability was neither reduced in more complex discrimination tasks such as distinguishing hexanal from octanal ( Fig.…”
Section: No Olfactory Deficits Detected In Ano2 -/-Micesupporting
confidence: 79%
“…4e) showed no change in the amount of tyrosine hydroxylase in the olfactory bulb, either. The expression of this enzyme depends on neuronal activity and was severely reduced in the olfactory bulb of anosmic Cnga2 -/y mice 30 . OSN axon coalescence on glomeruli is perturbed in mice lacking functional CNG channels 31 or the adenylate cyclase 32 .…”
Section: No Change Of Key Proteins and Axonal Convergencementioning
confidence: 98%
See 1 more Smart Citation